Peran Literasi Digital dan Literasi AI dalam Mendukung Technology-Enhanced Learning pada Mahasiswa Pendidikan Ekonomi Universitas Negeri Makassar - Andi Asti Handayani; Tuti Supatminingsih (MASALIQ, 2026)
The development of digital technology and artificial intelligence (AI) has driven the transformation of learning in higher education through the Technology-Enhanced Learning (TEL) approach. However, the successful implementation of TEL is determined not only by the availability of technology but also by students’ ability to use technology effectively. This study aims to analyze the role of Digital Literacy and AI Literacy in supporting Technology-Enhanced Learning among Economic Education students at Universitas Negeri Makassar. This study used a quantitative approach with a cross-sectional survey design. The research sample consisted of 90 students selected using purposive sampling. Data were collected through a questionnaire and analyzed using multiple linear regression with the assistance of the JASP application. The results showed that all instruments were valid and reliable, and the data met the assumptions of normality, linearity, multicollinearity, and heteroscedasticity. Partially, Digital Literacy and AI Literacy had positive and significant effects on Technology-Enhanced Learning. Simultaneously, both variables also had a significant effect on Technology-Enhanced Learning, with a coefficient of determination of 34.5%. Digital Literacy had a more dominant effect than AI Literacy. The conclusion of this study affirms that improving students’ digital and AI competencies is an important factor in supporting the effectiveness of technology-based learning. The implications of this study provide practical contributions for higher education institutions in strengthening digital literacy and AI literacy through curriculum development and learning strategies that are adaptive to technological transformation.